2005
DOI: 10.1242/jeb.01676
|View full text |Cite
|
Sign up to set email alerts
|

Energy costs of blood digestion in a host-specific haematophagous parasite

Abstract: Fleas consume and digest blood from their hosts. We hypothesized that the energy costs of digestion of blood by fleas is dependent on the host species. To test this hypothesis, we studied CO 2 emission, a measure of energy expenditure, during digestion of a blood meal taken by Parapulex chephrenis from a preferred (Acomys cahirinus) and a non-preferred (Gerbillus dasyurus) host. We predicted that the energy cost of digestion would be lower for A. cahirinus blood than that for G. dasyurus. Male and female fleas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 36 publications
4
56
1
Order By: Relevance
“…Our calculation of the RQ from stop-flow measures of oxygen consumption and carbon dioxide emission rendered values around 0.83 for resting insects, which is close to the consensus value of 0.8 that has been assumed by several authors when only carbon dioxide was measured (Lighton et al, 1993;Sarfati et al, 2005;Lighton, 2008). This value is within the classical interval resulting from burning lipids, proteins and sugar.…”
Section: Unexpectedly Low Respiratory Coefficientsupporting
confidence: 87%
See 2 more Smart Citations
“…Our calculation of the RQ from stop-flow measures of oxygen consumption and carbon dioxide emission rendered values around 0.83 for resting insects, which is close to the consensus value of 0.8 that has been assumed by several authors when only carbon dioxide was measured (Lighton et al, 1993;Sarfati et al, 2005;Lighton, 2008). This value is within the classical interval resulting from burning lipids, proteins and sugar.…”
Section: Unexpectedly Low Respiratory Coefficientsupporting
confidence: 87%
“…It is worth noting that the quantitative analysis of different feeding parameters in several species of haematophagous insects has revealed that they usually feed easier on the host with which they are naturally associated than on other vertebrates (Guarneri et al, 2000;Sarfati et al, 2005). Hence, not only does haematophagous feeding have a cost, but it should also vary with alimentary eclecticism.…”
Section: Feeding Is Costlymentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in flea feeding time is related to between-species differences in the time necessary for the majority of individuals to complete the blood meal successfully. This time was established for P. chephrenis and X. ramesis from our earlier studies (Sarfati et al, 2005;Khokhlova et al, 2008;Khokhlova et al, 2009a;Khokhlova et al, 2009c). After collecting fleas from a rodent, we examined the midgut of each flea under a light microscope (without dissection) to verify whether a flea took a blood meal and, if yes, to confirm the blood digestion status.…”
Section: Methodsmentioning
confidence: 99%
“…We suppose that, in the present study, access to food and blood quality (hence host quality) are the stressors for fleas (Tryjanowski and Adamski 2007). Digestion of blood is energetically costly, hence may affect the parasite body (Sarfati et al 2005). Moreo-…”
Section: Directional Asymmetrymentioning
confidence: 95%